Formin is associated with left-right asymmetry in the pond snail and the frog - Davison, Angus; McDowell, Gary S.; Holden, Jennifer M.; Johnson, Harriet F.; Koutsovoulos, Georgios D.; Liu, M. Maureen; Hulpiau, Paco; Roy, Frans Van; Wade, Christopher M.; Banerjee, Ruby; Yang, Fengtang; Chiba, Satoshi; et al. (Elsevier (Cell Press), 2016)
While components of the pathway that establishes left-right asymmetry have been identified in diverse animals, from vertebrates to flies, it is striking that the genes involved in the first symmetry-breaking step remain wholly unknown in the most obviously chiral animals, the gastropod snails. Previously, research on snails was used to show that left-right signalling of Nodal, downstream of symmetry-breaking, may be an ancestral feature of the Bilateria. Here we report that a disabling mutation in one copy of a tandemly duplicated, diaphanous-related formin is perfectly associated with symmetry-breaking in the pond snail. This is supported by the observation that an anti-formin drug treatment converts dextral snail embryos to a sinistral phenocopy, and in frogs, drug inhibition or over-expression by microinjection of formin has a chirality-randomizing effect in early (pre-cilia) embryos. Contrary to expectations based on existing models, we discovered asymmetric gene expression in 2 and 4 cell snail embryos, preceding morphological asymmetry. As the formin-actin filament has been shown to be part of an asymmetry-breaking switch in vitro, together these results are consistent with the view that animals with diverse bodyplans may derive their asymmetries from the same intracellular chiral elements.